Chronic abnormal uterine bleedings and quality of women's life. How to significantly improve the result? - Н. Ю. Педаченко; Т. М. Тутченко; Р. А. Тухтарян (Publishing House TRILIST, 2020)
Purpose of the study: to determine the effect of iron and vitamin D subsidies on the quality of women's life who receive pathogenetic therapy for abnormal uterine bleedings (AUB) caused by adenomyosis and/or endometrial polyps. Materials and methods. 114 patients with chronic AUB were randomized into two groups. The main group consist of 58 women, including 46 women with chronic AUB and adenomyosis (AUB-A), 12 women with adenomyosis and endometrial polyps (AUB-A,P). Women with AUB-A were prescribed 2 mg dienogest daily for the treatment of adenomyosis, similarly to patients with AUB-A,P after hysteroresection. All women in the main group also took a vitamin complex (iron, folate, iodine, vitamin D3, docosahexaenoic acid). The control group included 56 patients (43 women with AUB-A, 13 women with AUB-A,P) who were prescribed etiopathogenetic treatment (dienogest 2 mg per day and/or hysteroresection for endometrial polyps) without a vitamin complex subsidy. Quality of life was assessed using the SF-36 questionnaire. All patients received serum concentrations of hemoglobin, ferritin and 25(OH)D before and 3 months after treatment. Results. Iron-free dienogest therapy led to an increase serum hemoglobin levels after 3 months (p = 0.001). After three months vitamin complex Pregna-5 added there were significantly increased of hemoglobin levels, ferritin and 25(OH)D. This is accompanied by an improvement in the overall indicator of physical (r = 0.421, p <0.05) and psychological health (r = 0.385, p <0.05) on the SF-36 scale. An increase in serum ferritin greatly improves the psychological (r = 0.660, p <0.05) and physical components of women's health (r = 0.522, p <0.05). Optimization of serum vitamin D levels improves physical health (r = 0.494, p <0.05). Conclusions. It is necessary to combine etiopathogenetic therapy with additional sources of vitamin D and iron for successful therapy of AUB and restoration of deficient conditions. This is significantly improves the quality of life.